Water Balance Study in a Watershed of Malwa Region - Ranade, D.H.; Singh, J.; Tomar, A.S. (Journal of Soil and Water Conservation, 2022)
In a study, different components of water balance equations have been worked out for a treated watershed of Malwa region. It has been estimated that net recharge to the ground water body is of the extent of 0.639 m while the evapotranspiration is in the range of 0.003m. An appreciable amount of moisture storage remains in the black soil of this watershed